In vitro virulence determinants, comparative pathogenicity of Diutina (Candida) mesorugosa clinical isolates and literature review of the D. rugosa complex. (4th May 2019) - Montoya, Alexandra M.; Luna-Rodríguez, Carolina E.; Gracia-Robles, Gabriela; Rojas, Olga C.; Treviño-Rangel, Rogelio de J.; González, Gloria M.
ABSTRACT: Opportunistic mycoses by yeasts have increased considerably in the last three decades. Although Candida albicans is considered one of the most important causes of nosocomial infections, there is a recent shift to non- albicans Candida species as the most frequently isolated yeasts in particular risk groups. Diutina rugosa (formerly Candida rugosa ) is a complex that includes four species: D. rugosa sensu stricto, D. neorugosa, D. pseudorugosa, and D. mesorugosa, and they are estimated to represent 0.2% of all Candida clinical isolates. In this study, we analyze nine clinical isolates of D. mesorugosa with focus on the virulence determinants and pathogenicity of the species by means of a Galleria mellonella survival model. Overall, we detected very strong aspartyl-protease and esterase activities. In contrast, both DNase and hemolysin activities were evident in only two of the isolates. None of the isolates was positive for phospholipase activity. All isolates studied were able to form biofilm after 72 h of incubation in a robust manner when compared with the C. albicans strain used as control. Susceptibility testing showed minimum inhibitory concentrations (MICs) ≤1 µg/mL for amphotericin B in all isolates tested. Eight out of nine of the isolates had MICs ≤2 µg/mL for fluconazole. All isolates were resistant to both anidulafungin and caspofungin (MICs ≥1 µg/mL). We found a significant difference ( P < 0.0001) amongst the survival curves for the different D. mesorugosa isolates in the Galleria mellonella survival model. Strains HPM309 and H259 produced an acute infection and exhibited the highest virulence, whereas the D. mesorugosa isolates 99-480 and DM17 proved to be the less virulent strains.